Avaliação do orçamento público para efetivação dos direitos fundamentais: condições da teoria da reserva do possível - Lima, Ildevânia Félix de (2023)
The present dissertation has as its object the discussion about the costs of human rights and guarantees from a reflection on Public Policies and the Theory of the Reserve of the Possible, since the State alleges the insufficiency of financial and budgetary resources, sheltered by this theory, which expresses the scarcity of state resources, in which positive actions by the state itself are needed. In this case, the general objective focuses on evaluating the Brazilian public budget as a public policy in order to implement fundamental social rights, following the idea that the State has, in its financial activities, a limited capacity to program and implement policies. with the purpose of allocating financial resources efficiently and coherently between government priorities and the public budget. For this, it is necessary to: Verify elements in the public budget (participatory budget and legal norms on financial law and public budget) inserted in the Brazilian democratic and social context; identify government priorities between 2015 and 2022; and to analyze the discourse of the Brazilian State in the adoption of the Theory of the Reserve of the Possible, showing its possible contradictions and political agendas. Therefore, the dissertation starts from an evaluative approach to the public budget based on the discussion of counter-hegemonic paradigms, having in this perspective the political evaluation of Ozanira Silva, so that one can refer to the political agendas and the evaluative models of the neoliberal agenda, in which it is possible to show the contradictions of the State itself. It is proposed to carry out this research based on bibliographical and documentary studies of a quali- quanti nature, with the quantitative method carried out by vertically and horizontally descriptive statistics of budgetary data extracted from the Government Transparency Portals. Qualitatively, this research uses theories about the main categories of analysis, through books and scientific articles from CAPES e Scielo.Where there is a research gap regarding the approach to the object of this study, since most of the research carried out on the public budget deals more with the econometric and efficiency aspects that measure the quality of public spending, not being, therefore, interested in the aspects of the intentionalities of budgetary policies.In addition, it is of a documentary type, with the analysis of the Federal Constitution of 1988, the National Tax Code, the Fiscal Responsibility Law, the budgetary laws and other pertinent regulations. Therefore, for the evaluation of the public budget, considering all its problems, for the realization of rights, the objectives of this work include a broadening of the political, analytical and methodological horizon, which is glimpsed in an idea of non-conformity of the policy with the orthodox parameters and hegemonic.The main results achieved suggest that budget policies are conducted under the political-ideological aspects of neoliberalism, which justifies the use of the possible reserve for the application of financial resources in social policies. The reserve of the possible, therefore, is included in these neoliberal practices, which hinders the effectiveness of fundamental rights.